The Principle People's Sovereignty as Basic Rule of The Minimum Age Limit for President and Vice President Candidates - Putra, Marsudi Dedi (UNISKA LAW REVIEW, 2024)
Equality are the essence of the principles of popular sovereignty. In Indonesia, the principle of popular sovereignty has been transformed and formulated into a legal basis in statutory regulations. However, setting the minimum age limit for Presidential and Vice Presidential Candidates has actually created injustice. This research aims to explain the principle of popular sovereignty in relation to the minimum age limit for presidential and vice presidential candidates. This type of research is normative juridical, with a prescriptive normative approach apart from being based on state teachings. The analysis was carried out normatively qualitatively. Research results: (1) A country that adheres to the principle of popular sovereignty wants every public position to be open and to provide equal and equal opportunities for every citizen to achieve it, including the positions of President and Vice President. (2) The regulation that limits the minimum age to 40 years as a requirement for candidates for President and Vice President is an action that violates human rights, is less sensitive to changes and the legal needs of society, and is not in accordance with the essence of popular sovereignty.